Síntese de compostos heteroazóicos substituídos no solvente alternativo PEG 400 - Ferreira, Achiles Silva (2018)
The present work describes the development of a simple and efficient methodology for the synthesis of 2-aminoheteroazoic compounds using the solvent PEG 400 as an alternative to toxic and flammable organic solvents. Several media and reactional conditions were compared. A series of substituted 2-aminothiazoic compounds was obtained in good yields (60 to 96%) by a 3 hour reaction procedure using PEG 400 at room temperature and without the need for additives or catalysts. A selenium analogue and a 2-imino-1,3-thiazoline were also obtained by this method. The products were characterized by 1H and 13C NMR and infrared spectroscopies and mass spectrometry. The method covers some points of Green Chemistry, such as: safe synthesis, prevention in the formation of residues or derivatives, development of products that do not harm the environment, energy efficiency and accident prevention.